Anaerobic Biotransformation of Aromatic and Polycyclic Aromatic Hydrocarbons in Soil Microcosms: A Review - R. Karthikeyan; A. Bhandari (Journal of Hazardous Substance Research, 2001)
Industrial activities introduce a wide variety of xenobiotic aromatic compounds into the biosphere. These aromatic and polycyclic aromatic compounds find their way into anaerobic marine and freshwater sediments, saturated aquifers, and waterlogged soils where neither their impact on carbon flow nor their propensity to persist is clearly understood. Although some halogenated aromatic compounds are degraded via anaerobic pathways, anaerobic transformation of aromatics remains limited to a small range of chemicals. This paper reviews anaerobic transformation processes for aromatic compounds, particularly polycyclic aromatic hydrocarbons (PAHs) in soil microcosms. A simplified pathway of PAH biotransformation and a conceptual pathway of PAH degradation under different redox-conditions are presented.
Keywords: bioremediation; denitrification; PAHs; sulfidogenesis